2008
DOI: 10.1089/thy.2007.0370
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Autoimmunity in Schoolchildren in an Area with Long-Standing Iodine Sufficiency: Correlation with Gender, Pubertal Stage, and Maternal Thyroid Autoimmunity

Abstract: These findings demonstrate that thyroid antibody positivity in children was significantly associated with maternal autoimmunity and their development in girls emerges at puberty. Since heredity, female gender, and puberty are strongly associated with TA, girls in families with TA should be examined at the onset of puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
3
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 38 publications
5
35
3
5
Order By: Relevance
“…Radetti et al (77) found high levels of TPOAb in nearly 24% of overweight or obese children. This prevalence is similar to that observed in children with type 1 diabetes mellitus (21.6%) (123) and outnumbers current epidemiologic data in iodine-sufficient schoolchildren, which indicate a TPOAb prevalence in the range of 3.4-4.6% (124,125).…”
Section: European Journal Of Endocrinologysupporting
confidence: 86%
“…Radetti et al (77) found high levels of TPOAb in nearly 24% of overweight or obese children. This prevalence is similar to that observed in children with type 1 diabetes mellitus (21.6%) (123) and outnumbers current epidemiologic data in iodine-sufficient schoolchildren, which indicate a TPOAb prevalence in the range of 3.4-4.6% (124,125).…”
Section: European Journal Of Endocrinologysupporting
confidence: 86%
“…It is, however, interesting to note that another type of autoimmunity has high incidence periods at a later age; seroconversion to TPO autoantibodies was frequent in this cohort, but did not reach high levels until puberty and appeared to peak in adolescence. The thyroid organ undergoes remodelling around this age as a result of increased activity [22][23][24], potentially explaining the increased rate of TPO autoimmunity. Interestingly, neonatal remodelling of the pancreas has been suggested to be involved in the pathogenesis of diabetes in the NOD mouse [25].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, studies (66)(67)(68)(69) have found that 3-13% of adults have TgAb. However, in children, the prevalence of TgAb is lower (70,71), and Zimmermann et al (47) suggest that screening for TgAb in this age group is not necessary. Twenty-two of 34 studies measured TgAb prior to Tg measurement (Table 1).…”
Section: Methods To Measure Tg Concentrationmentioning
confidence: 99%